Six-month IVUS and two-year clinical outcomes in the EVOLVE FHU trial: a randomised evaluation of a novel bioabsorbable polymer-coated, everolimus-eluting stent. - Meredith, I; Verheye, S; Weissman, N; Barragan, P; Scott, D; Chávarri, M; West, N; Kelbæk, H; Whitbourn, R; Walters, D; Kubica, J; Thuesen, L; et al. (2013)
Aims: The EVOLVE FHU trial demonstrated non-inferiority of six-month late loss with two dose formulations of SYNERGY, a novel bioabsorbable polymer everolimus-eluting stent (EES) compared with the durable polymer PROMUS Element (PE) EES. The current analysis describes the six-month IVUS and clinical results through two years from the EVOLVE FHU trial. Methods and results: EVOLVE recruited 291 patients from 29 centres. At six months, IVUS-assessed in-stent net volume obstruction was 3.40±5.06% for PROMUS Element (PE) vs. 2.68±4.60% for SYNERGY (p=0.34) and 3.09±4.29% for SYNERGY ½ dose (p=0.68 vs. PE). There were no significant differences between groups for any other measured IVUS parameter including resolved, persistent, and late-acquired incomplete stent apposition (ISA). At two years, target lesion failure (TLF) was 6.1% for PE vs. 5.5% for SYNERGY (p=0.87) and 5.2% for SYNERGY ½ dose (p=0.81). There were no significant differences between groups for cardiac death, repeat revascularisation, MI or stent thrombosis through two years. Conclusions: At six months, everolimus delivered from an ultrathin bioabsorbable abluminal polymer resulted in equivalent net volume obstruction and ISA compared with a permanent polymer EES. There were no significant differences between PE and either SYNERGY stent for any major cardiac endpoint through two years. Clinical trials number: NCT01135225.